In Vogue: Ketamine for Neuroprotection in Acute Neurologic Injury - Bell, Josh D (Anesthesia and analgesia, 2017)
Neurologic deterioration following acute injury to the central nervous system may be amenable to pharmacologic intervention, although, to date, no such therapy exists. Ketamine is an anesthetic and analgesic emerging as a novel therapy for a number of clinical entities in recent years, including refractory pain, depression, and drug-induced hyperalgesia due to newly discovered mechanisms of action and new application of its known pharmacodynamics. In this focused review, the evidence for ketamine as a neuroprotective agent in stroke, neurotrauma, subarachnoid hemorrhage, and status epilepticus is highlighted, with a focus on its applications for excitotoxicity, neuroinflammation, and neuronal hyperexcitability. Preclinical modeling and clinical applications are discussed.